South American Cucurbit Fruit Fly, Anastrepha grandis (Macquart) (Insecta: Diptera: Tephritidae) - Howard V. Weems (EDIS)
This rather large, yellow-brown, fruit fly with yellow and dark-brown markings exists in several South American countries, and attacks watermelon and other fruits of the family Cucurbitaceae. Once a pest of minor to moderate importance generally, it has become a rather important pest. The pest status differs in each country and has sometimes changed within a country. This species is potentially of economic importance in Florida and southern Texas should it ever be introduced there. It has been intercepted in the United States in pumpkin from Argentina and Brazil, and in banana debris from Panama. This revised 3-page fact sheet was written by H. V. Weems, Jr., and published by the UF Department of Entomology and Nematology, March 2012.